The Role of the Notary Honorary Council on the Confiscation of Minutes of Deed by Police Investigators - Ahmad Ramadan; Amin Purnawan; Lathifah Hanim (Sultan Agung Notary Law Review, 2022)
The purpose of this study was to identify and analyze the role of the notary honorary council in the confiscation of the minutes of deed by the Southeast Sulawesi regional police investigators. And to find out and analyze the process of examining a criminal case allegedly carried out by a notary with the offense of entering false information in an authentic deed. The research method usedis a sociological juridical method. The sociological juridical research method is legal research that uses secondary data as initial data which is then continued with primary data in the field or on the community, examines the effectiveness of a ministerial regulation and research that wants to find a relationship (correlation) between various symptoms or variables, as a data collection tool consists of from the study of documents or library materials and interviews. The results of this study found that: first, the Regional Notary Honorary Council from the results of the examination by the examining council could not give approval for the confiscation of the minutes of the notary deed but gave permission to the investigator to take a photocopy of the minutes of the notary deed. Second, from the results of the examination by the examining board, there was also no offense of entering false information into the minutes of the deed. Even from the results of the examination it was also found that the complainant did not question the contents of the deed, but what was questioned was his absence at the General Meeting of Shareholders (GMS), and in the minutes of the GMS there was the signature of the reporter which indicated that the reporter was present at the GMS and the Reporting Party itself was also present.